INFLUÊNCIA MICROCLIMÁTICA DE FLORESTA URBANA AO SEU ENTORNO IMEDIATO: BOSQUE DA COMUNIDADE EM BAURU-SP - Lima, João Victor de Souza; Tonon, Beatriz Frasão; Oneto, Marina Simões Moss; Faria, João Roberto Gomes de; Fontes, Maria Solange Gurgel de Castro (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The expansion of cities changes the morphology of urban space and, consequently, its urban microclimates. In Bauru downtown, a remnant densely wooded park, the Bosque da Comunidade, attenuates the microclimatic rigors of its surroundings. The objective of this research was to evaluate the microclimatic influence of this urban forest on its immediate surroundings, enriching the knowledge obtained by previous works on that area. Data was collected at a fixed point in the interior of the forest, synchronized with data collection on 24 mobile points in its immediate surroundings, succeeded by correlations and comparative analysis. It was verified the effective contribution of the woodland to its immediate surroundings, regarding the mitigation of the thermal loads by shading, evaporative cooling, and the creation of negative pressure zones that allow natural ventilation.